Band positions of anatase (001) and (101) surfaces in contact with water from density functional theory - Geiger, Julian; Sprik, Michiel; May, Matthias M. (Journal of Chemical Physics, 2020)
Titanium dioxide in the anatase configuration plays an increasingly important role in photo(electro)catalytic applications due to its superior electronic properties when compared to rutile. In aqueous environments, the surface chemistry and energetic band positions upon contact with water determine charge-transfer processes over solid-solid or solid-electrolyte interfaces. Here, we study the interaction of anatase (001) and (101) surfaces with water and the resulting energetic alignment by means of hybrid density functional theory. While the alignment of band positions favors charge-transfer processes between the two facets for the pristine surfaces, we find the magnitude of this underlying driving force to crucially depend on the water coverage and the degree of dissociation. It can be largely alleviated for intermediate water coverages. Surface states and their passivation by dissociatively adsorbed water play an important role here. Our results suggest that anatase band positions can be controlled over a range of almost 1 eV via its surface chemistry.
CRIS-Team WoS Importer:2020-06-16